COMMUNICATION STYLE OF REGIONAL HEAD IN HANDLING COVID 19 THROUGH TWITTER SOCIAL MEDIA, 2021-2022 - Umayah, Difa; Rahmawati, Dian Eka (Universitas Muhammadiyah Yogyakarta, 2022)
This study aimed to analyze regional heads' communication styles during the COVID-19 pandemic through the Twitter accounts @ganjarpranowo and @ridwankamil. This study uses a qualitative research approach. The data was obtained through the Twitter accounts @ganjarpranowo and @ridwankamil. The study results found that the intensity of twitter on the two accounts from April 2021 to March 2022 in 2021-2022 proves that the increase in COVID-19 cases is relatively increasing, so it is necessary to provide information by regional heads in conveying to the public. This effort shows the communication style represented by the two leaders of Central Java and West Java through indicators: controlling, equalizing, structuring, dynamic, letting go, and withdrawing. The communication style developed by the two regional heads during the COVID-19 pandemic through the Twitter accounts @ganjarpranowo, and @ridwankamil actively conveys related information to the public so that the information provided is adequately obtained; this can be seen in the communication style of communication through associated indicators. Regarding the communication style used by Ganjar Pranowo and Ridwan Kamil, each has advantages related to the communication style used by Ganjar Pranowo is more Equalitarian, while Ridwan Kamil is dynamic; both leaders have their respective advantages.